2023
DOI: 10.1038/s41598-023-38030-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soil-transmitted helminth infections in HIV patients: a systematic review and meta-analysis

Abstract: Soil-transmitted Helminth (STH) infections have been found associated with people living with human immunodeficiency virus (HIV) but little is known about the overall burden of STH coinfection in HIV patients. We aimed to assess the burden of STH infections among HIV patients. Relevant databases were systematically searched for studies reporting the prevalence of soil-transmitted helminthic pathogens in HIV patients. Pooled estimates of each helminthic infection were calculated. The odds ratio was also determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…(1) According to the World Health Organization (WHO), in 2022, Soil-transmitted helminths infections are among the most common infections worldwide with an estimated 1.5 billion infected people worldwide. (2) Since the early 1990s, the semi-autonomous archipelago of Zanzibar in the United Republic of Tanzania has been marked by a high prevalence of soil-transmitted helminths. In the 2000s, the Zanzibar Ministry of Health reported that an estimated 1 million people on Zanzibar (Unguja and Pemba) are infected with STHs.…”
Section: Introductionmentioning
confidence: 99%
“…(1) According to the World Health Organization (WHO), in 2022, Soil-transmitted helminths infections are among the most common infections worldwide with an estimated 1.5 billion infected people worldwide. (2) Since the early 1990s, the semi-autonomous archipelago of Zanzibar in the United Republic of Tanzania has been marked by a high prevalence of soil-transmitted helminths. In the 2000s, the Zanzibar Ministry of Health reported that an estimated 1 million people on Zanzibar (Unguja and Pemba) are infected with STHs.…”
Section: Introductionmentioning
confidence: 99%